Technical education performance Inspection (III): analysis of documents - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2014)
The management teams and teachers prepare documents for the design and development planning, implementation and evaluation of educational processes and management of schools and; Periodically, the inspectors analyzed, evaluated and, if necessary, report drafts, memoranda, schedules and records that are part of them. The objective is to obtain knowledge about the organization and operation of the centers and the process of teaching and learning in their classrooms continues to carry out its monitoring, evaluation and counseling. This technique requires a careful and thorough reading of the documents and an appraisal of its contents. Gathered this information, you need to check it and complete it by applying other techniques. In this article a brief analysis of the document analysis is performed. At its regular work, the education inspectorate rarely used programs and applications available but to ensure the rigor of the process and the validity of the conclusions drawn, it is essential to follow a series of steps and phases that are described below.